Evaluation of psychopathology en adult victins if political emprisonment and torture during their adolescence and childhood - Jorquera, María José; Briones, Michelle; Valencia, César; Contreras, María Eliana (Revista Chilena de Salud Pública, 2011)
Objective: Evaluate the presence of psychopathology indicators in adults who were political prisoners during childhood and/or adolescence, during the Chilean military dictatorship. Materials and methods: Case studies and controls, in which indicators of mental disorders were compared in three groups: A) adults who suffered torture and have not received psychosocial treatment, B) adults who suffered torture who did receive psychosocial treatment, and C) adults whose adolescence and/or childhood took place during the dictatorship, who did not suffer torture. A nonrandom sample of 60 people was used. Indicators of depression, anxiety (state/trait), post traumatic stress syndrome (PTSD) and personality disorder were measured with specific scales. Results: There are significant differences in the indicators of mental disorder studied, between those adults who suffered torture and those that did not. Nevertheless, there are not significant differences between those that received psychosocial treatment and those that did not. Conclusions: There is an association between external trauma in childhood and/or adolescence, and psychopathology in adults, and that the possibility of disorders becoming chronic or not depends on interacting social variables.